Environmental policymaking : assessing the use of alternative policy instruments - Hatch, Michael T., 1945- (State University of New York Press, 2005)
The methods employed in the pursuit of environmental protection are often highly contested. Leading to alternative policy approaches. This book details the frequently neglected topic oc these alternative approaches to environmental policymaking through casestudies drawn primarily from the United States, Germany, and Japan. Among the policy instruments analyzed are eco-audits, voluntary agreements, tradable permits, green taxes, environmental impact assessments, and command and control regulations. Also examined are international regulatory arrangements to encourage sustainble forestry management practoces. Various evaluative criteria are applied to each case study, including environmental effeectiveness, economic and political efficiency, administrative efficacy, and technological innovation.